Pensando a educação em chave decolonial: um olhar a partir das produções dos programas em educação da UFRRJ - Borges, Willinis Eziquiel (2024)
The main objective of this master's dissertation is to analyze how the decolonial inflection is present in the dissertations of Universidade Federal Rural do Rio de Janeiro based on the productions available in the Biblioteca Digital Brasileira de Teses e Dissertações. This study is configured as a literature review. To carry out this investigation, we followed the data collection criteria outlined by Lima and Mioto (2007). These criteria encompass the thematic parameter, which involves the search for works related to our research area, namely dissertations from the graduate programs in education at Universidade Federal Rural do Rio de Janeiro; the linguistic parameter, restricting the research to publications in Portuguese; the source, which focuses on the theses and dissertations available in the Biblioteca Digital Brasileira de Teses e Dissertações repository; and the chronological parameter, in which we established all dissertations available until December 2023. In the theoretical framework, we intend to trace a brief genealogy of decolonial thought through the lens of the Modernity/Coloniality Group, trying to conceptualize some of the proposals of this group. Subsequently, we present the analysis conducted on the identified works.